Irisin Is Controlled by Farnesoid X Receptor and Regulates Cholesterol Homeostasis - Li, Hong; Shen, Jing; Wu, Tong; Kuang, Jiangying; Liu, Qinhui; Cheng, Shihai; Pu, Shiyun; Chen, Lei; Li, Rui; Li, Yanping; Zou, Min; Zhang, Zhiyong; et al. (Frontiers in Pharmacology, 2019)
Objective The aim of this study was to investigate whether the nuclear receptor farnesoid X receptor(FXR) could regulate FNDC5/Irisin expression and the role of Irisin in hyperlipidemia and atherosclerosis in ApoE-/-mice. Methods and results We treated primary human hepatocytes, HepG2 cells and Rhesus macaques with FXR agonist (CDCA, GW4064 and ivermectin). FNDC5 expression was highly induced by CDCA and GW4064 in hepatocytes, HepG2 cells and the circulating level of Irisin increased in Rhesus macaques. Luciferase reporter and CHIP assays were used to determine whether FXR could regulate FNDC5 promoter activity. Irisin-ApoE-/- and ApoE-/-mice were used to study the metabolic function of Irisin in dyslipidemia and atherosclerosis. Irisin-ApoE-/- mice showed improved hyperlipidemia and alleviated atherosclerosis as compared with ApoE-/- mice. Irisin upregulated the expression of Abcg5/Abcg8 in liver and intestine, which increased the transport of biliary cholesterol and fecal cholesterol output. Conclusion Activation of FXR induces FNDC5 mRNA expression in human and increased the circulating level of Irisin in Rhesus macaques. FNDC5/Irisin is a direct transcriptional target of FXR. Irisin may be a novel therapeutic strategy for dyslipidemia and atherosclerosis.